Dissemination of Staphylococcus epidermidis in Swedish bovine dairy herds: minimal overlap with human isolates - Persson Waller, Karin; Myrenås, Mattias; Kim, Hyeyoung; Widerström, Micael; Monsen, Tor; Börjesson, Stefan; Östlund, Emma; Cha, Wonhee (Frontiers in Microbiology, 2025)
Knowledge of zoonotic links between bovine and human isolates of Staphylococcus epidermidis remains limited. The primary aim of this study was to assess the genetic relatedness of S. epidermidis isolates from bovine subclinical mastitis (SCM), bovine milk filters, healthy dairy farmers or farm personnel, and human hospital patients in Sweden, and to detect and compare genes encoding antimicrobial resistance (AMR) and virulence factors. A secondary aim was to explore the epidemiology of bovine S. epidermidis intramammary infections (IMI) by examining associations between genotypes and geographic location, persistence of IMI, severity of inflammatory response, and the persistence of S. epidermidis strains over time. A total of 283 S. epidermidis isolates were analyzed using whole genome sequencing (WGS): 128 SCM milk isolates, 55 milk filter isolates, 13 farmer/personnel isolates, and 87 human patient isolates. Sixty unique sequence types (STs) of S. epidermidis were identified. ST99, ST100, and ST570 were the most common among bovine isolates, collectively accounting for 49% (63/128) of the milk isolates and detected on multiple farms, while ST2 and ST215 were the most prevalent among human isolates. Only four STs (ST59, ST73, ST184, and ST218), representing a total of 13 isolates, were found in both bovine and human samples. Genes conferring AMR were more frequently identified in human patient isolates compared to bovine isolates. However, penicillin resistance, identified by presence of the blaZ gene, was detected in 42% of bovine S. epidermidis isolates. The average number of potential virulence factors (pVF) per isolate was 23.8 with 23.1 in milk isolates, 23.4 in milk filter isolates, 23.0 in farmer/personnel isolates, and 25.2 in human patient isolates. There was some variation in the total number of pVFs and the presence of specific pVFs or functional groups of pVFs between sample types and STs. In conclusion, the results indicate that the overlap of STs and AMR genes between human and bovine samples was minimal. However, the persistence of certain STs across multiple dairy farms suggests inter-farm transmission. This study provides new insights into the epidemiology of bovine S. epidermidis IMI, with implications for the control of these infections.